Vergangenheit, die nicht vergeht Das Gedächtnis der Shoah in Frankreich seit 1945 im Medium Film - Schmoller, Andreas (Studien Verlag, 2010)
The publication entitled "Vergangenheit, die nicht vergeht. Das Gedächtnis der Shoah in Frankreich seit 1945 im Medium Film" (A past, that doesn't pass. Holocaust Memory in France since 1945 in the Media Film) explores the basic transformations of the Holocaust-memory in France on the basis of French fiction films that are to be identified as part of cinematography of the Holocaust. The chosen approach that can be described as a history of memory referring to models of collective memory in cultural science studies. The aim is to specify the change of collective memory at the level of the particular filmic narratives and - by doing so - to identify and to analyze the long term development and ruptures in the French culture of remembrance since 1945. The empiric part of this study is preceded by methodological reflections that on the one hand permit a clear and differentiating application of the terms used in the current cultural studies of collective memory. On the other hand this chapter should help to conceive the material of research "Fiction Film" as primal source for historical science. The investigation is divided into five chronological parts and involves altogether a sample of 50 films into the general study before electing cases for deeper analyses.